Factors Related to Tuberculosis Treatment Compliance: A Cross-Sectional Study on Pulmonary Tuberculosis Patients - Swarjana, I Ketut; Ansan, Yoseph Maurits; Rismawan, I Made; Barata, Agus (Babali Publisher, 2024)
Introduction: The success of pulmonary TB treatment remains low due to patients' lack of compliance with the treatment regimen. This study aims to determine factors related to treatment compliance among TB patients at the Internal Medicine Outpatient Clinic of the Raja Ampat Regional General Hospital. Methods: An observational research design with a cross-sectional study approach was employed, involving 125 tuberculosis patients receiving treatment at the Internal Medicine Outpatient Clinic of the Raja Ampat Regional General Hospital, selected through total sampling technique. Data collection utilized a structured questionnaire. Data were analyzed using univariate, bivariate (Chi-Square test), and multivariate (Binary Logistic Regression) analyses. Results: The majority of treatment-compliant TB patients among the 125 respondents were 74 (59.2%) in the compliant category. There was a significant relationship between age, education, knowledge, attitude, perception, motivation, and staff support with the level of treatment compliance. Good knowledge (AOR: 2.18; CI: 1.05-1.56; p 0.003) and high staff support (AOR: 1.27; CI: 1.11-1.68; p 0.006) increased TB patient treatment compliance. Conclusion: TB patient treatment compliance is still below the established standards. Knowledge and staff support enhance better treatment compliance, emphasizing the importance of education and improving service access, such as health worker visits to TB patients' homes.